Peran Perempuan Dalam Gerakan Dakwah Islam - Faizah, Rohmatul; Alkhalimi, Diva Vidia (Ahsan: Jurnal Dakwah dan Komunikasi, 2023)
Women have an important position in Islam. Before the arrival of Islam, women did not have any role in society, but since Islam came with its teachings, women have had the same roles and positions as men, including in missionary activities both in their families and in society. In the time of the Prophet Muhammad, the important role of women in seeking knowledge and teaching it had been seen since the time of Siti Khadijah and Siti Aisyah. Until the modern era, the important role of women in da'wah is still significant, to provide understanding on fiqh issues, family problems, education and other problems which are the duties and responsibilities of women. Therefore, this study reveals the role of women's da'wah as da'iyah. Using a qualitative approach, researchers used literature data to examine the role of women in da'wah. The results of this study show that women have had a strategic role in da'wah from the time of the prophet until now.